Cloning of K26 Hydrophilic Antigen from Iranian Strain of Leishmania infantum - HOSSEINI FARASH, Bibi Razieh (Iran J Public Health, 2017)
BACKGROUND: Visceral leishmaniasis (VL) caused by Leishmania infantum is the most severe form of leishmaniasis in Iran, which causes a high mortality rate in the case of inaccurate diagnosis and treatment. This study aimed to clone of K26 gene from Iranian strain of L. infantum and register the sequencing results in Genbank to facilitate the preparation a new K26 antigen for the detection of L. infantum infection. METHODS: L. infantum was obtained from an infected domestic dog in Meshkin-Shahr area from northwestern Iran in 2015. Canine visceral leishmaniasis was confirmed by direct agglutination test (DAT), rK39 dipstick and parasitological methods. L. infantum was confirmed by N-acetyl glucosamine -1-phosphate transferase (nagt)–PCR and its sequencing. The band of interest for k26 form Iranian strain of L. infantum was purified by gel extraction kit after PCR amplification and then ligated into pBluescript II SK (+) and pET-32a (+), respectively. The sequences of recombinant plasmids were analyzed and submitted to Genbank. RESULTS: The submission of rk26 nucleotide sequence was performed to the GeneBank/NCBI Data Base under accession number KY212883. The related gene was showed a homology about 99% to L. chagasi and L. infantum k26 gene, while the level of homology in comparison with different strains of L. donovani ranged from 84–94%. CONCLUSION: The successful rk26 cloning into an expression vector performed in this study could help to produce a new recombinant antigen for serodiagnosis of VL especially in areas where L. infantum is the main causative agent.